Komunikasi Interpersonal pada Keluarga Beda Budaya - Sanadi, Debora Ria (Jurnal The Messenger, 2014)
The aim of the research to know different cultural family to decide what s the best solution to soulve different of opinion.  The theory base used in this research is quoted from Richard and Larry, who stated that communication from one culture and the receifer is a member from the other.  Population in this research is spouse who have different cultural. While the sample only one family.  It is concluded that, different cultural that must be a comitmen made before married, so there will be understanding each other because when two people from two defferent cultural has married, they also unite the culture.